Annotating legal documents with GaiusT 2.0. (2017) - Zeni, Nicola; Mich, Luisa; Mylopoulos, John
We present the GaiusT 2.0 framework for annotating legal documents. The framework was designed and implemented as a web-based system to semi-automate the extraction of legal concepts from text. In requirements analysis these concepts can be used to identify requirements a software system has to fulfil to comply with a law or regulation. The analysis and annotation of legal documents in prescriptive natural language is still an open problem for research in the field. In GaiusT 2.0, a multistep process exploits a number of linguistic and technological resources to offer a comprehensive annotation environment. The modules of the system are presented as evolutions from corresponding modules of the original GaiusT framework, which in turn was based on a general-purpose annotation tool, Cerno. The application of GaiusT 2.0 is illustrated with two use cases, to demonstrate the extraction process and its adaptability to different law models.